The Oil Content andthe Diatom Density in TanjungTiram Waters of Batu Bara Regency, North Sumatera Province - Bahri S, Aswan; Amin, Bintal; Siregar, Sofyan Husein (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT  This research was conducted on july 2018  in Tanjung Tiram Waters of Batu Bara regency, North Sumatera province. It aims to analyze the oil content  and  the diatom density.The sample was analyzedin the Marine Chemistry and Marine Biology Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The survey method used in this research was purposive which consisted of four stations. Each station is repeated in three times. It known that the oil content in water ranged 0,1722 – 0,4341 ppm.According to standard quality value of sea water, the oil content of water has not exceeded the threshold value (<5 ppm). The results of calculating the abundance of diatoms are known to be the highest in station 4 with the number 144 ind / l, while the lowest abundance of diatoms is at station 1 with a number of 97 ind / l. The mostof diatom species found is Nitzschia sp., Skeletonema sp., Leptocylindrus sp., and Coscinodiscus sp.Based on the level of fertility, the abundance of the diatoms in TanjungTiram area is categorized as oligotrophic waters, namely waters that have a low fertility level with a range between 0 - 2000 ind / l.The correlation of oil content and the diatom density are declared in mediocrevalue with coefficient of 0.53.   Key words : Pollution, Oil Content, Diatom, North Sumatera